2017
DOI: 10.1016/j.anireprosci.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of porcine stem cell competence for somatic cell nuclear transfer and production of cloned animals

Abstract: Porcine somatic cell nuclear transfer (SCNT) has been used extensively to create genetically modified pigs, but the efficiency of the methodology is still low. It has been hypothesized that pluripotent or multipotent stem cells might result in increased SCNT efficacy as these cells are closer than somatic cells to the epigenetic state found in the blastomeres and therefore need less reprogramming. Our group has worked with porcine SCNT during the last 20 years and here we describe our experience with SCNT of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It is worth highlighting that the genetically engineered (OE-OCT6) iPSCs, whose capability to differentiate in vitro was considerably attenuated by transgenically increasing the relative abundance of OCT6 transcripts and extrinsic OCT6 proteins, may provide an excellent source of nuclear donor cells (NDCs) suitable for somatic cell nuclear transfer (SCNT)-based assisted reproductive technologies in pigs and other mammalian species ( Gorczyca et al, 2021 ; Olivera et al, 2016 ; Samiec & Skrzyszowska, 2010 ; Secher et al, 2017 ; Zhang et al, 2014 ). Highly reprogrammable NDCs may exhibit an enhanced capacity to sustainably perpetuate stemness- and pluripotency-related molecular attributes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth highlighting that the genetically engineered (OE-OCT6) iPSCs, whose capability to differentiate in vitro was considerably attenuated by transgenically increasing the relative abundance of OCT6 transcripts and extrinsic OCT6 proteins, may provide an excellent source of nuclear donor cells (NDCs) suitable for somatic cell nuclear transfer (SCNT)-based assisted reproductive technologies in pigs and other mammalian species ( Gorczyca et al, 2021 ; Olivera et al, 2016 ; Samiec & Skrzyszowska, 2010 ; Secher et al, 2017 ; Zhang et al, 2014 ). Highly reprogrammable NDCs may exhibit an enhanced capacity to sustainably perpetuate stemness- and pluripotency-related molecular attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Given a need for an appropriate model system to facilitate the discovery of drugs, in the present study, using SCNT following rAAV-mediated gene targeting, we developed a DMD exon 52-deleted miniature pig model that shows a lack of dystrophin protein bodywide and a severe phenotype. As we previously reported [ 48 ], the cloning technology of SCNT is an effective method for generating transgenic piglets compared to other methods with porcine embryonic stem cells and induced pluripotent stem cells, which have some limitations such as cell isolation difficulty, incomplete reprogramming, and a lower rate of embryonic development in pigs [ 49 , 50 , 51 ]. The present study indicates that the SCNT combined with gene targeting by the rAAV vector used here can facilitate generation of DMD models with pigs harbouring genetic mutations of interest, together with other genetic engineering technologies such as genome editing [ 28 , 29 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that nuclear reprogramming was improved when BM-MSCs were used because of their multipotent capacity. While some articles defend the idea that there is no correlation between the stemness of the cell and the cloning efficiency, 45 47 others have demonstrated that the differentiation status influences the developmental potential of the reconstructed embryos. There are many studies that observed higher developmental rates of the embryos when less-differentiated cells were used compared to fully differentiated cells as nuclear donors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cloning with iPSCs as nuclear donors in domestic animals has not been promising, in spite of their pluripotent capacity. 16 , 47 , 49 , 50 These differences between the efficiencies of MSCs and iPSCs may be related to the resident expression of the exogenous pluripotent genes oct4, cmyc, klf4 and sox2 in integrative iPSC lines, 16 , 51 the suboptimal culture conditions 52 or the difficulties regarding cell cycle synchronization of the iPSCs which could compromise the success of cloning. 53 In contrast, MSCs are multipotent stem cells that are easy to maintain in culture and behave similar to fibroblasts in vitro, which facilitates their manipulation and cell cycle synchronization.…”
Section: Discussionmentioning
confidence: 99%